The effect of psychoeducation with health coaching method on HbA1c levels Among Type 2 Diabetes Mellitus - Minarti Minarti; Supriyanto Supriyanto; Miadi Miadi; Ach. Arfan Adinata; Nikmatul Fadilah (PAGEPress Publications, 2024)
Different dangerous and life-threatening complications, such as hypoglycemia, hyperglycemia, and metabolic ketoacidosis are caused by uncontrolled Diabetes Mellitus (DM). Therefore, this study aimed to analyze the effect of psychoeducation with health coaching methods in type 2 DM patients on HbA1c levels. In this context, a quasi-experimental design was adopted with pre-and post-test control group methods. The sample size for the intervention and control groups was 30 type 2 DM patients who were routinely controlled at the Kalijudan Surabaya Community Health Center between March to April 2023 using a simple random sampling method. The intervention group received psychoeducational intervention using the health coaching method with six sessions through 3 meetings and module media, while the control only received module education media. Furthermore, the HbA1c level was taken before and after intervention, and the effect was measured using the t-test. The results showed that pre-test and post-test HbA1c levels were decreased (mean 9.06; 5.98) and increased (mean 9.13; 10.59) in the intervention and control groups, respectively. Psychoeducation with the health coaching method and provision of modules to patients was more effective compared to groups only given modules (0.000). In conclusion, this intervention motivated patients subjected to treatment, facilitated increased personal control, and built confidence in managing diabetes independently. The implication obtained was an increase in the ability of patients to make self-care decisions.